Universalism, materialism and class politics: Notable absences in critical psychology - Mackintosh, Raphael (PINS-Psychology in Society, 2018)
[ B O O K R E V I E W ] Parker, Ian (ed) (2015) Handbook of critical psychology. Hove & New York: Routledge. ISBN 978-1-84872-218-7 hbk. Pages xv + 477 Group work has become essential to the modern economy, where most projects are too wide-ranging for a single pair of hands, or, when it comes to intellectual labour, too grand for an individual intelligence to cover in all their detail (Coetzee & Kurtz: 2015). More often than not such projects are organized from the beginning in modular fashion: the final aim is broken down into a series of modules, each of which is then assigned to an independent worker or team to complete. This division of labour, which usually involves following instructions “from above” while being isolated from one’s co-workers, ensures that when the group project is complete, there is no one person who knows precisely how all the parts relate to the finished product as a whole. Indeed, the work-experience of a group preoccupied with a modular project “may be as alienated as that of an individual worker in the factories of Victorian Britain”, as Marx and Engels once keenly observed (Coetzee & Kurtz, 2015: 120).